MODERN FOOD RETAIL AND UNFAIR TRADING PRACTICES - Popović, Vesna; Mihailović, Branko; Simonović, Zoran (Economics of Agriculture, 2018)
The abuse of bargaining power by retailers is reflected in unfair trading practices (UTPs) and there has been a growing interest among EU MSs to address them using regulatory approach and self-regulatory initiatives among market participants. The experiences of ex-YU and neighboring EU MSs are of interest for Serbia. Serbian food suppliers are not protected from UTPs apart from general competition and contract rules and payment terms regulation. Therefore, after a brief review of the global food retail trends and the role of power in the supply chain management in the introduction, the discussion focuses on UTPs and regulatory mechanisms to address them at the EU level, in selected EU MSs and in Serbia. Regarding existing EU and MS practices, it is recommended that Serbia introduce specific UTP regulation in the food supply chain and authorize the Commission for Protection of Competition for the enforcement.